Study of the Association between Allergic Rhinitis and Asthma among Libyan Children - Elzigallai O and Alrabty H* (AlQalam Journal of Medical and Applied Sciences, 2020)
Background and objectives: Allergic rhinitis is common association to asthma according to worldwide studies which showed that control of allergic rhinitis improves in turn asthma symptoms so we have conducted this study looking for the percent of allergic rhinitis in Libyan asthmatic children who were attending regular follow up in asthma clinic of Tripoli children hospital over period of one year (2008). Methods: This study was conducted by asking children’s parents using questionnaire composed of directly answered questions (yes or no) if their children got attacks of rhinorrhea, nasal itching and sneezing around certain times of the year (spring and autumn). Results: Conclusively we found that the incidence of allergic rhinitis in asthmatic Libyan children was 36.6%. Conclusion: allergic rhinitis is common with asthma, and it needs to be put in consideration in any asthma patient and treated accordingly.